Bibliometric Evaluation of 2012–2020 Publications on Ferroptosis in Cancer Treatment - Zhou, Qian; Wu, Fei; Zhao, Mingyi; Yang, Minghua (Frontiers in Cell and Developmental Biology, 2022)
Ferroptosis is an iron-dependent programmed cell-death caused by the accumulation of lipid peroxides, which is different from apoptosis, autophagy, necrosis and other forms of regulatory cell death in morphology and mechanism. It has attracted interest and attention of scholars from all over the world during the past years. Recent studies have shown that ferroptosis is able to play a clear and important role in cancer treatment, providing a bright prospect for targeted cancer therapy. This article aims to analyze current scientific results about the application of ferroptosis in the field of cancer treatment, providing new ideas for further research. We retrieved publications related to ferroptosis and cancer treatment from 2012 to 2020 from the Web of Science Core Collection (WoSCC), screening them according to the inclusion criteria. A total of 965 related papers were included, and the total number of publications increased year by year. We used CiteSpace 5.7.R2, VOSviewer and Microsoft Excel 2019 to evaluate and visualize the results, analyzing institutions, countries/regions, journals, authors, co-cited reference and keywords. Overall, with more and more evidence showing the indispensable role of ferroptosis in cancer, its mechanism research and target discovery may become the main direction of future research.